Effectiveness of Preoperating Teaching with Anxiety Levels in Preoperating Sectio Caesarea Patients - Wulandari, Siswi; Erike Yunicha Viridula; Weni Tri Purnani; Vivitri Yulinda; Raras Sucma A (Journal for Quality in Public Health, 2023)
Surgery is an experience that can cause anxiety.  Anxiety is a feeling of fear that is unclear and not supported by the situation. In lowering anxiety, health education is needed. The purpose of the study was to analyze the effect of Pre Operating Teaching (Informed Consent) with anxiety levels in preoperative sectio caesarea patients in the Maternity Room of Arga Husada Hospital, Kediri, Malang Regency. Pre-experimental research design with pre-test and post-test design approaches. The population of all maternity mothers with sectio caesarea in the Maternity Room of Arga Husada Kediri Hospital was 120 people and a sample of 93 people with accidental sampling techniques. The research variables are Pre Operating Teaching and anxiety levels. HARS checklist and questionnaire instruments for anxiety. Data analysis using the Mc Nemar test.  The results of the Mc Nemar statistical test showed a significance  value of 0.0 00  (p<0.05) there was an effect  of pre-operating teaching  with the level of anxiety of pre-operative sectio caesaria patients  in the maternity room. The conclusion of this study is that the administration of pre-operating teaching can significantly reduce anxiety levels in SC preoperative patients. The anxiety that preoperative patients experience is due to a psychological condition that feels that it is not possible to express something unknown and the anticipation of something unknown and possible painful procedures will be the most common main cause. The anxiety facedis due to ignorance of the surgical procedure, the impact of the operation and the condition after undergoing surgery. Therefore, informed consent is needed to reduce the patient's anxiety about the threats that the patient feels when he is about to undergo surgery. Based on the results of this study, it is recommended to midwives to provide informed consent in accordance with the SPO applicable in the hospital.